Proyek Optimalisasi Media Sosial Instagram dalam Meningkatkan Konversi Konsumen Warung Tilu Nini - Jessica Lois Simamora; Yusandrina Farisha; Raden Rifqi Dwisanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Warung Tilu Nini is a local culinary business that serves Indonesian home cooking with a traditional yet modern concept. In facing the challenges of limited physical space and low levels of social media interaction, this project aims to optimize digital marketing strategies through the Instagram platform to increase consumer conversion. The methods used are direct observation, interviews, and analysis of social media insight data before and after the campaign. The strategies designed include creating relevant visual content, utilizing Instagram features such as Reels and Stories, and collaborating with local micro-influencers. The results of implementing this strategy show a significant increase in the number of followers, engagement rates, and interactions that drive sales conversions, especially for takeaway and catering services. These findings prove that targeted social media optimization can be an effective solution in encouraging the growth of culinary MSMEs in the digital era.